Recombinant expression and characterization of the cytoplasmic rice β-glucosidase Os1BGlu4. - Chen Rouyi (Public Library of Science (PLoS), 2014)
The Os1BGlu4 β-glucosidase is the only glycoside hydrolase family 1 member in rice that is predicted to be localized in the cytoplasm. To characterize the biochemical function of rice Os1BGlu4, the Os1bglu4 cDNA was cloned and used to express a thioredoxin fusion protein in Escherichia coli. After removal of the tag, the purified recombinant Os1BGlu4 (rOs1BGlu4) exhibited an optimum pH of 6.5, which is consistent with Os1BGlu4's cytoplasmic localization. Fluorescence microscopy of maize protoplasts and tobacco leaf cells expressing green fluorescent protein-tagged Os1BGlu4 confirmed the cytoplasmic localization. Purified rOs1BGlu4 can hydrolyze p-nitrophenyl (pNP)-β-D-glucoside (pNPGlc) efficiently (kcat/Km  =  17.9 mM(-1) · s(-1)), and hydrolyzes pNP-β-D-fucopyranoside with about 50% the efficiency of the pNPGlc. Among natural substrates tested, rOs1BGlu4 efficiently hydrolyzed β-(1,3)-linked oligosaccharides of degree of polymerization (DP) 2-3, and β-(1,4)-linked oligosaccharide of DP 3-4, and hydrolysis of salicin, esculin and p-coumaryl alcohol was also detected. Analysis of the hydrolysis of pNP-β-cellobioside showed that the initial hydrolysis was between the two glucose molecules, and suggested rOs1BGlu4 transglucosylates this substrate. At 10 mM pNPGlc concentration, rOs1BGlu4 can transfer the glucosyl group of pNPGlc to ethanol and pNPGlc. This transglycosylation activity suggests the potential use of Os1BGlu4 for pNP-oligosaccharide and alkyl glycosides synthesis.